An Exploration of University Students’ Challenges in Learning English as a Foreign Language (EFL) During COVID-19 Pandemic - Siti To'ifah; Fatimah Mulya Sari (TEKNOSASTIK, 2022)
Since the COVID-19 virus outbreak emerged in the world, all industries and aspects of life have changed, including the education system. Face-to-face learning was compelled to be replaced with online learning. Online Learning has made students experience integrating technology into the teaching and learning process. Technological and environmental problems can lead to challenges that may be faced by the students, especially in learning English as a foreign language. Thus, this study was conducted with the aim to identify the challenges that EFL students faced in learning English as a foreign language during the COVID-19 pandemic, as well as describe the students’ strategies to overcome the challenges. This study was designed as a qualitative study. To conduct the study, 10 students of English education major of Universitas Teknokrat Indonesia were invited to be the subject. By reason of study from home, an unstructured online interview about the objectives was conducted via the WhatsApp application. This study finding indicated that the most common issue faced by EFL students in this situation is internet access, followed by a lack of learning media, material understanding, academic dishonesty, and laziness.